Fostering Women's Empowerment through Men’s Involvement in Family Planning Initiatives and Effective Strategies: A Systematic Review - Susmita Mukherjee; Dr. Archna Kumar, (Indian Journal of Social Science and Literature (IJSSL), 2024)
Family planning is one of the most important aspects of family health and welfare. Men's engagement in family planning is a critical component in promoting women's empowerment. In this study, we conducted a systematic review following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines to explore the multifaceted dynamics shaping the relationship between men's involvement in familial planning initiatives and women's empowerment. A systematic search was conducted in the Scopus database, employing carefully selected keywords such as "women* empowerment", "female empowerment," "empowerment of women", "male", "men*", "family planning", "contraceptive practices", "birth control", "reproductive health," "pregnancy prevention", and "planned parenthood" on January 30, 2024. The study provides a comprehensive insight into men's involvement in family planning globally and in India, revealing a need for significant social change to address bias favouring men in resource allocation. The findings emphasize the efficacy of modular survey approaches, particularly in capturing indicators related to antenatal care and contraceptive method usage. Globally, successful interventions like mass media campaigns and participation in maternal and child health programs were identified, emphasizing the importance of tailored approaches to cultural contexts and the need for cross-cultural learning. Overall, the results highlight the multifaceted nature of men's involvement in family planning and its crucial role in advancing women's empowerment.